The Effect of Android-Based Self Care Management on Self Efficacy and Control of Fasting Blood Sugar Levels of People with Type 2 Diabetes Mellitus in the Working Area of the Tempel Sleman Health Center - Agustina Retno Hapsari; Mardiyono Mardiyono; Suharsono Suharsono (Eduvest - Journal of Universal Studies, 2025)
Controlling glycemic levels can be achieved through disciplined self-care management, which significantly enhances self-efficacy in individuals managing diabetes mellitus. This study examines the impact of an Android-based health mobile application on empowering type 2 diabetes sufferers, improving nursing services, and optimizing time and cost efficiency. The quasi-experimental research employed a randomized control trial design, conducted at the Tempel II Community Health Center in Sleman, Yogyakarta, from November to December 2023. The findings reveal that Android-based self-care management serves as an effective educational tool, leading to improved self-efficacy among participants. Key components include meal planning, which emphasizes the consumption of carbohydrates, vegetables, proteins, fats, and fruits, and regular physical activity exceeding 150 minutes. Notably, no significant differences were observed in pharmacological interventions. Evaluations indicated substantial improvements in self-efficacy and fasting blood sugar control post-intervention. Overall, the integration of self-care management across five pillars—education, blood sugar monitoring, nutritional therapy, physical exercise, and pharmacological adherence—demonstrated a significant positive effect on glycemic control in type 2 diabetes patients within the Tempel Sleman Community Health Center area.